Life cycle thinking strategies for constructing nZEB schools - Elisabetta Palumbo; Rosa Romano; Paola Gallo (Agathón)
By 2050, Italy, too, will have to achieve climate neutrality. Compared to current standards, almost 75% of the existing building stock is energy inefficient, and since 17% consists of school buildings, intervening in this type of building is essential to develop virtuous paths to achieve 2030 decarbonisation targets. Vertical envelopes are among the technological units that contribute the most to achieving better energy-environmental performance of the building, but at the same time, they have a certain weight in terms of carbon and embodied energy; moreover, LCA studies dealing with the vertical building envelope mainly focus on ‘cradle-to-grave’ impacts, neglecting end-of-life scenarios based on the recycling of selective demolition materials. This study explores the effects of adopting circular design strategies as LCA-based environmental impacts in an nZEB school.